Structural and dielectric properties of cobaltacarborane composite polybenzimidazole membranes as solid polymer electrolytes at high temperature. Issue 15 (29th March 2018) - Fuentes, Isabel; Andrio, Andreu; García-Bernabé, Abel; Escorihuela, Jorge; Viñas, Clara; Teixidor, Francesc; Compañ, Vicente
Abstract : The conductivity of a series of composite membranes based on PBI containing the metallacarborane salts M[COSANE] and M[TPB] has been investigated. Abstract : The conductivity of a series of composite membranes, based on polybenzimidazole (PBI) containing the metallacarborane salt M[Co(C2 B9 H11 )2 ], M[COSANE] and tetraphenylborate, M[B(C6 H5 )4 ], M[TPB] both anions having the same number of atoms and the same negative charge, has been investigated. Different cations (M = H +, Li + and Na + ) have been studied and the composite membranes have been characterized by water uptake, swelling ratios, ATR FT-IR, thermogravimetric analysis and electrochemical impedance spectroscopy to explore the dielectric response and ion dynamics in composite membranes. Our results show that conductivity increases with increasing temperature and it is higher for H + than for Li + and Na + for all temperatures under study. The mobility of Li + is greater in [COSANE] − than in [TPB] − composite PBI@membranes while for Na + it is the opposite. The temperature dependence of the conductivity of the composite was followed by a typical Arrhenius behaviour with two different regions: (1) between 20 and 100 °C, and (2) between 100 and 150 °C. Using the analysis of electrode polarization (EP) based on the Thrukhan theory we have calculated the ionic diffusion coefficients and the density of carriers. From the double logarithmic plot of the imaginary part of the conductivity ( σ ′′) versus frequency in the entire range of temperatures studied we have determined for each sample at each temperature, the frequency values of the onset ( f ON ) and full development of electrode polarization ( f MAX ), respectively, which permit us to calculate static permittivity.